A Single-phase Inverter Based on Full-bridge Modules With Input in Series-connection and Outputs Coupled by a Multiple-winding Transformer - Ruseler, Adriano; Lazzarin, Telles Brunelli; Barbi, Ivo (Eletrônica de Potência, 2015)
This paper proposes an isolated modular single–phase inverter for high–input voltage applications. The topology is composed of conventional and modular full–bridge inverters with series–connected inputs and magnetically–connected outputs. All input bus capacitors are connected in series and thus the dc voltage is divided among the inverter modules. The full–bridge outputs are connected by a multiple–winding low– frequency transformer, the inverters employ a typical three–level modulation with phase–shift carriers and when an appropriate modulation is used a multilevel output voltage is supplied for the load. The auto–balance of the input capacitor voltages is verified and a harmonic analysis is performed in order to investigate the exchange of active and reactive power between the inverter modules at low and high frequency. An 8 kW prototype with three modules, a multiple–winding transformer with a transform ratio of 1:1:1:1, 1200 V dc input source and 220 V/ 60 Hz ac output voltage was built and tested in order to verify the proposed topology.